Effectiveness Of Scratch Learning in Elementary School Social Studies Digitalized Era - Diyas Age Larasati; Anna Roosayanti (LPPM Universitas PGRI Sumatera Barat, 2024)
Scratch is very beneficial for children in developing logical thinking. This study aims to determine the effectiveness of Scratch in elementary school social studies learning in the digital era. This research was conducted at SDN Sawocangkring. The research population of class IV AC was 93 students. The sample was selected purposively, resulting in a sample of 62 students in class IV-A and IV-B. This type of research was quantitative with a quasi-experimental design. Class IV-A was the experimental class, while class IV-B was the control class. The experimental class used scratch media for learning, while the control class used powerpoint media. This research instrument used pretest and posttest on social studies material with the same questions in the form of multiple choice questions totaling 25 items. Data analysis used the T test with the help of SPSS 2.5.0 for Windows. Because the Sig. (2-tailed) value = 0.000 < 0.05, then H₀ is rejected. And H₁ is accepted. This means there is a significant difference between the pretest and posttest results after using Scratch learning media. In addition to improving scores, student engagement also increased. Researchers noted that during the learning process using Scratch, students appeared more active in discussing, asking questions, and collaborating in creating simple animation projects on social studies themes.